The efficacy and safety of the training process in sumo through autogenic training for professional wrestlers - Yuliya Holenkova; Leonid Vostroknutov; Pavol Bartik (Pedagogy of Health)
Background and purpose of the study. Considering the high demands for physical and psychological preparedness in sumo, the implementation of comprehensive approaches to training becomes relevant. Such an approach ensures the improvement of sports results and the health maintenance of athletes. The study is aimed at analyzing the effectiveness of autogenic training in the educational and training process among experienced sumo wrestlers.